2018
DOI: 10.1111/jgh.14526
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic acid attenuates colitis‐associated colon cancer by inhibiting nuclear factor kappaB signaling

Abstract: Background and Aim Inflammatory bowel diseases is associated with an increased risk for the development of colorectal cancer. However, the mechanism of immune signaling pathways linked to colitis‐associated cancer (CAC) has not been fully elucidated. Tauroursodeoxycholic acid (TUDCA) exhibits anti‐inflammatory and anti‐cancer activities. The aim of this study is to investigate the role of TUDCA in the pathogenesis of CAC. Methods Colitis‐associated cancer was induced in mice using azoxymethane and dextran sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Whereas, in a mice model of CACC, TUDCA-mediated diminution of cancer development was dependent on the reduction of phosphorylated IκB kinase and extensive epithelial apoptosis in the colon of treated animals [181]. Additionally, in TNF-α-stimulated HCT116 cells, TUDCA markedly decreased the expression of IL-8 and IL-1α and inhibited TNF-α-induced phosphorylation/degradation of IκBα together with suppression of NF-κB DNA-binding activity [181]. These studies suggest that TUDCA is able to ameliorate tumorigenesis mostly via alleviation of NF-κB-mediated inflammatory response, thus paving the way for chemopreventive use of this bile acid in oncogenesis of certain carcinomas.…”
Section: Tudca In Cancermentioning
confidence: 85%
See 3 more Smart Citations
“…Whereas, in a mice model of CACC, TUDCA-mediated diminution of cancer development was dependent on the reduction of phosphorylated IκB kinase and extensive epithelial apoptosis in the colon of treated animals [181]. Additionally, in TNF-α-stimulated HCT116 cells, TUDCA markedly decreased the expression of IL-8 and IL-1α and inhibited TNF-α-induced phosphorylation/degradation of IκBα together with suppression of NF-κB DNA-binding activity [181]. These studies suggest that TUDCA is able to ameliorate tumorigenesis mostly via alleviation of NF-κB-mediated inflammatory response, thus paving the way for chemopreventive use of this bile acid in oncogenesis of certain carcinomas.…”
Section: Tudca In Cancermentioning
confidence: 85%
“…Thus, it seems counterintuitive to use chemical chaperones such as TUDCA in cancer research, since their cytoprotective potential would rather benefit in maintaining neoplastic cells instead of eliminating them. Paradoxically, several reports from in-vitro and in-vivo studies inform that TUDCA/UDCA might have some favorable effects in therapy of certain types of cancer [175][176][177][178][179][180][181]. Early studies of the influence of TUDCA on growth of human cholangiocarcinoma Mz-ChA-1 cell line demonstrated that TUDCA suppressed the growth of the Mz-ChA-1 cells due to increased calcium signaling and downstream activation of PKC-α-and MAPK p42/44-dependent pathways [175].…”
Section: Tudca In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, blocking the NF-κB pathway is an idea for the future treatment of CRC. Oroxylin A [19], GEN-27 [20], tauroursodeoxycholic acid (TUDCA) [21] and an ethanol extract obtained from the aerial parts of Artemisia princeps Pampanini cv. Sajabal (EAPP) have been verified as a blocker of the NF-κB pathway, which would inhibit CRC.…”
Section: Il-1βmentioning
confidence: 99%